2021
DOI: 10.1177/1358863x20978468
|View full text |Cite
|
Sign up to set email alerts
|

Inframalleolar bypass for chronic limb-threatening ischemia

Abstract: The aims of this study were to analyze the results of inframalleolar bypass for chronic limb-threatening ischemia (CLTI) and to identify outcome-predicting factors. All consecutive patients undergoing inframalleolar bypass for CLTI between 2015 and 2018 were included in this retrospective, single-center study. Outflow artery was the most proximal patent vessel segment in continuity with inframalleolar arteries. Bypasses originating from the popliteal artery were defined as ‘short bypasses’. Sixty patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, in extreme circumstances, bypasses are also done to inframalleolar arteries such as plantar and tarsal arteries [6]. Although inframalleolar bypass is technically challenging, acceptable limb salvage rates have been reported [3]. The usual target arteries for such bypasses are dorsalis pedis, or even plantar arteries [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in extreme circumstances, bypasses are also done to inframalleolar arteries such as plantar and tarsal arteries [6]. Although inframalleolar bypass is technically challenging, acceptable limb salvage rates have been reported [3]. The usual target arteries for such bypasses are dorsalis pedis, or even plantar arteries [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although inframalleolar bypass is technically challenging, acceptable limb salvage rates have been reported [3]. The usual target arteries for such bypasses are dorsalis pedis, or even plantar arteries [3]. In extreme situations, bypasses are also done to the named collateral arteries such as descending genicular artery or median sural artery [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benedetto and colleagues report on their experience with inframalleolar bypass in patients with advanced CLI. 11 These findings emphasize the need to consider all available options when attempting limb salvage in CLI. Endovascular techniques and devices have also significantly advanced in the past few years.…”
mentioning
confidence: 92%
“…In lower extremity arterial disease, the femoropopliteal artery has a larger lumen and is often treated with intervention combined with drugs; meanwhile, the distal small artery intervention is more difficult, and drug therapy or surgery is mainly used ( 4 ). Benedetto et al demonstrated that inframalleolar bypass resulted in good patency rates, limb salvage and overall survival ( 5 ). Currently, two main methods are used for interventional treatment of femoropopliteal artery disease, namely, stent implantation and balloon dilation ( 4 ) followed by strict medical therapy, including long-term antiplatelet therapy and statin ( 6 ).…”
Section: Introductionmentioning
confidence: 99%